GE_GERICHTE C/14166/2010 vom 7. Oktober 2016 - GE Cour de justice (2016)
NOUVEAU MOYEN DE PREUVE ; COURTAGE ; INTERPRÉTATION(SENS GÉNÉRAL) ; PROVISION(COMMISSION) ; SIMULATION ; FARDEAU DE LA PREUVE | CPC.317.1; CPC.317.2; CO.18.1; CO.412; CO.413.1;